The E3 ubiquitin ligases regulate PD-1/PD-L1 protein levels in tumor microenvironment to improve immunotherapy - Hou, Bo; Chen, Ting; Zhang, He; Li, Jiatong; Wang, Peter; Shang, Guanning (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) is the tumor surrounding environment, which is critical for tumor development and progression. TME is also involved in clinical intervention and treatment outcomes. Modulation of TME is useful for improving therapy strategies. PD-L1 protein on tumor cells interacts with PD-1 protein on T cells, contributing to T cell dysfunction and exhaustion, blockage of the immune response. Evidence has demonstrated that the expression of PD-1/PD-L1 is associated with clinical response to anti-PD-1/PD-L1 therapy in cancer patients. It is important to discuss the regulatory machinery how PD-1/PD-L1 protein is finely regulated in tumor cells. In recent years, studies have demonstrated that PD-1/PD-L1 expression was governed by various E3 ubiquitin ligases in TME, contributing to resistance of anti-PD-1/PD-L1 therapy in human cancers. In this review, we will discuss the role and molecular mechanisms of E3 ligases-mediated regulation of PD-1 and PD-L1 in TME. Moreover, we will describe how E3 ligases-involved PD-1/PD-L1 regulation alters anti-PD-1/PD-L1 efficacy. Altogether, targeting E3 ubiquitin ligases to control the PD-1/PD-L1 protein levels could be a potential strategy to potentiate immunotherapeutic effects in cancer patients.